Walking, talking, playing: Children with disabilities’ outdoor play in French mainstream schools - Clémence Orain; Thomas Morgenthaler; Christina Schulze (Scandinavian Journal of Occupational Therapy)
Background Children’s right to play remains underexplored in French mainstream schools. France’s inclusive education policies aim to include children with disabilities in mainstream classrooms, but this transition can create challenges hindering meaningful play opportunities. This highlights the importance of gaining a deeper understanding of children’s experiences of play in school playgrounds.Aim This study explores children with disabilities’ experiences and perspectives on their outdoor play in French mainstream school playgrounds.Material and Methods Walking and Talking tour interviews were conducted with thirteen children with various disabilities across six mainstream schools in western France. Data were audio-recorded, transcribed verbatim and analysed using thematic analysis.Results (1) ‘I can(not) play’: Environmental Barriers and Opportunities; (2) ‘I have an idea’: Children’s Preferences for Enriching Play and Inclusion; (3) ‘Learn to Hear Me Out’: Strengthening Children’s Participation in Everyday School Practices including Playground Redesign.Conclusions and Significance This study highlights the barriers children with disabilities face in French mainstream school playgrounds. It emphasises the need for collaborative co-design to create inclusive and playful environments. Findings have implications for occupational science, inclusive education, school-based occupational therapy, and urban design. Future participatory research should explore the co-design of school playgrounds, involving all relevant stakeholders.